2021
DOI: 10.3390/ijerph18073542
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Adolescent Communication, School Engagement, and Internet Addiction among Chinese Adolescents: The Moderating Effect of Rejection Sensitivity

Abstract: Although a large body of research has indicated that parent-adolescent communication is a crucial protective factor for adolescent Internet addiction, the mediating and moderating mechanisms underlying this relationship remain unclear. To address this research gap, this study, based on social control theory and the organism-environment interaction model, was designed to test whether school engagement mediated the relationship between parent-adolescent communication and adolescent Internet addiction and whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 60 publications
4
19
0
Order By: Relevance
“…This scale, developed by Young et al (2004) [40], is widely used to measure the level of Internet addiction among adolescents and has been proven to be reliable and valid in Chinese teenagers [7]. Items are scored on a three-point scale.…”
Section: Young's Diagnostic Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…This scale, developed by Young et al (2004) [40], is widely used to measure the level of Internet addiction among adolescents and has been proven to be reliable and valid in Chinese teenagers [7]. Items are scored on a three-point scale.…”
Section: Young's Diagnostic Questionnairementioning
confidence: 99%
“…Internet addiction not only seriously affects adolescents' normal study and life habits but also damages their physical and mental health development [4,5]. Internet addiction in adolescents has been attributed to lead to absenteeism, declining academic performance, depression, and even extreme ideas and behaviors, such as suicide and crime [6,7]. Therefore, practical remedial and prevention programs must be established, with consideration for the scientific identification of the protective and risk factors and underlying mechanisms for adolescent internet addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive internet use may exhibit similar patterns and have similar negative consequences to the life of youths and adolescents compared to other addictive behaviors ( Shapira et al, 2003 ; Young, 2004 ). From the parents’ perspective, the attachment of youths and adolescents to the internet may lead to the passivity in the young people’s daily activities, changes in their psychological states and behaviors, and negative effects on the quality of the parent–child relationship ( van Den Eijnden et al, 2010 ; Shek et al, 2018 ; Restrepo et al, 2020 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Millings et al (2012) among adolescents aged from 11 to 16, they found that being connected with school served as a protective factor against depression. The literature has also indicated that students with higher school engagement have a lower level of anxiety (Lester et al, 2013), loneliness (Al-Yagon et al, 2016), aggressive behavior (Chapman et al, 2011), suicidal ideation (Marraccini & Brier, 2017), delinquency (Lee et al, 2018), emotional stress (Resnick et al, 1997), dropout (Archambault et al, 2009), and internet addiction (Li et al, 2021). In addition to the negative relationship between school engagement and negative experiences, the literature has shown a positive relationship finding between school engagement and positive psychological outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…School engagement is closely associated with numerous behavioral, emotional, social, psychological, and academic outcomes (Libbey, 2004). Individuals with high school engagement are at lower risk for many negative experiences (Li et al, 2021; Wang & Fredricks, 2014; Wang & Peck, 2013; Zhu et al, 2019). In the study conducted by Millings et al (2012) among adolescents aged from 11 to 16, they found that being connected with school served as a protective factor against depression.…”
Section: Introductionmentioning
confidence: 99%